Use of silica fume and nano-silica in mortars attacked by acids present in pig manure - Jacob, Jefferson De Santana; Mascelani, Amadeu Grezzana; Steinmetz, Ricardo L.R.; Costa, Filipe Antonio Dalla [UNESP]; Dalla Costa, Osmar Antonio (My University, 2018)
Pig houses provide a highly aggressive environment to concrete structures. The chemical aggressiveness generated by pig manure may cause wear, loss in strength and premature damage to floors, leading to animal hoof diseases. Since the chemical attack in cementitious structures is controlled by its porosity and permeability, the use of mineral admixtures in cement is convenient. This work evaluated the behaviour of cement mortars with nano-silica and silica fume (micro-silica) to an acid attack, simulating the effects of acids present in pig manure to cementitious materials. Two cement mortars were tested: one with nano-silica as an additive and another with nano-silica and silica fume (cement replacement of 10%), as well as a control mortar with Portland cement. The mortars were submitted to acid attack cycles for four weeks. The compressive strength at 35, 50 and 65 days, mass loss and water absorption after 65 days were evaluated. Mortars containing nano-silica and silica fume showed considerable loss of workability, however showed the best performance in all studied aspects, indicating that the simultaneous use of these additions may result in longer-lasting concrete structures in pig houses.
Keywords: animal welfare; concrete; nano-silica; pig manure; silica fume